A rare entity in a pediatric patient: coexistence of emphysematous cystitis and emphysematous pyelonephritis - Agar, Buket Esen; Kara, Aslihan; Gurgoze, Metin Kaya; Eroglu, Yesim (Turkish J Pediatrics, 2023)
Background. Emphysematous cystitis (EC) and emphysematous pyelonephritis (EPN) are rare urinary tract infections. They have a wide spectrum of clinical manifestations; ranging from asymptomatic to septic shock at presentation. In children, EC and EPN are rare complications of urinary tract infections (UTIs). Their diagnosis is based on clinical manifestations, laboratory results and characteristic radiological findings of gas within the collecting system, renal parenchyma and/or perinephric tissue. Computed tomography is the best radiological option in the diagnosis of EC and EPN. Despite the availability of various treatment modalities including medical and/or surgical treatment alternatives, these life-threatening conditions have high mortality rates reaching up to 70 percent. Case. Urinary tract infection was detected in the examinations of an 11-year-old female patient suffering from lower abdominal pain, vomiting and dysuria for two days. Air was detected in the bladder wall on X-ray. EC was detected in the abdominal ultrasonography. Air formations in the bladder lumen and calyces of both kidneys in abdominal computed tomography confirmed the presence of EPN. Conclusions. Individualized treatment should be instituted according to the severity of EC and EPN, and the overall health condition of the patient.
Keywords: emphysematous pyelonephritis; emphysematous cystitis; Enterobacter aerogenes; child